Fish oil supplementation in chronic obstructive pulmonary disease: feasibility of conducting a randomised controlled trial. Issue 1 (December 2017) - Fulton, Ashley; Coates, Alison; Williams, Marie; Howe, Peter; Garg, Manohar; Wood, Lisa; Frith, Peter; Hill, Alison
Abstract Background Long-chain omega-3 polyunsaturated fatty acids (LCn-3PUFAs) may act as an effective adjunct therapy for chronic obstructive pulmonary disease (COPD), a condition characterised by persistent airflow limitation and inflammation. However, the nature of this illness presents challenges for evaluating potential benefits. The aim of this study was to determine the feasibility of undertaking a randomised controlled trial of LCn-3PUFA supplementation in adults with COPD. Methods A 16-week parallel, double-blind, randomised, placebo-controlled dietary supplementation trial was conducted. Participants diagnosed with COPD were randomly allocated to take six 1-g capsules of fish oil (3.6 g LCn-3PUFA) or corn oil (placebo) daily for 16 weeks. Key outcomes used to determine the feasibility of the trial included recruitment rate, participant retention rate and supplement adherence (blood biomarker and returned capsule count). An estimate of the effect size for clinical outcomes such as pulmonary function and functional exercise capacity was calculated. Results None of the key feasibility criteria were met. The enrolment target was 40 participants in 52 weeks; however, only 13 were finally enrolled, with just seven in the first 52 weeks. Eight participants completed the study (retention rate 62%). Targets for compliance were not achieved; red blood cell LCn-3PUFA content (expressed as percentage of total fatty acids) did not increase by more than 2% in the fish oil group; capsule counts were unreliable. As the target sample size was not achieved and only a small number of participants completed the study, it was not possible to use the variance in clinical outcomes to estimate a sample size for a future study. Conclusions This study highlights major difficulties, especially with recruitment, in conducting this LCn-3PUFA supplementation trial in people with COPD, rendering the protocol unfeasible by predetermined criteria. A modified approach is needed to investigate potential health benefits of fish oil in people with COPD. A multicentre study with changes to inclusion and exclusion criteria is recommended. Trial registration Australia and New Zealand Clinical Trials Register (ANZCTR), ACTRN12612000158864